A Techno-Economic Analysis of Space-Based Solar Power Systems - Benedikt Kruft (Junior Management Science (JUMS), 2023)
Space-based solar power (SBSP) promises to provide flexible renewable baseload power. However, no full-system prototype exists due to a perceived lack of economic viability. The goal of this thesis is therefore to determine how different technology approaches can improve key technical metrics of SBSP and consequently the economics. For this purpose, we divide the system into its three main segments and define critical metrics for the performance of each subsystem. Based on these, novel technology approaches from the literature are then evaluated. For the solar satellite, we are able to show that a number of technology options exist that might improve power levels, radiation resistance, and mass-related ratios. These advances would greatly benefit overall system economics, as the space segment constitutes a big lever for enhancing the levelised cost of electricity (LCOE). Furthermore, microwave power beaming efficiencies in line with required levels have been demonstrated but so far lack the scale and distance necessary for SBSP. Ultimately, the global capacity in space lift capabilities appears to be a major bottleneck. Consequently, a reduction in mass of the satellite would not only be a matter of economics but might render any such project even possible in the first place.
Keywords: 650; Energy; Solar; Space; Microwaves; Sustainability